Characterization of Temperate Actinophage φC31 Isolated from Streptomyces coelicolor A3(2) - Lomovskaya, N. D. (1972)
Actinophage φC31 isolated from Streptomyces coelicolor A3(2), the only strain among actinomycetes for which a genetic map had been constructed, appears to be a typical temperate phage. After φC31 infection, true lysogenic cultures arose which liberated phage and were immune to infection with homologous phage after repeated single-colony isolations and treatment with phage-specific antiserum. Clear-plaque (c) mutants were derived from φC31 phage which failed to lysogenize sensitive cultures. Actinophage φC31 has a temperature-sensitive stage of reproduction. A phage which reproduces with the same effectiveness at high (37 C) and low (28 C) temperatures has also been obtained. Heat-inducible (ct) mutants were isolated from this phage which were able to lysogenize sensitive cultures at 28 C but failed to do so at 37 C. Properties of ct mutants suggest that ct mutations involve a gene controlling maintenance of the lysogenic state in actinomycetes and synthesizing repressor, which may become heat-sensitive as a result of mutation.